Perforated diverticulitis: To anastomose or not to anastomose? A national survey. (2018) - Shaban, F.; Holtham, S.
Abstract: Introduction and Aims: No consensus has been reached in the management of perforated diverticulitis. However, many surgeons opt for a Hartmann's procedure. A primary anastomosis has been shown to be a feasible alternative. We hypothesize that colorectal consultants and senior trainees are more likely to opt for a resection with primary anastomosis in selected cases than their non-colorectal counterparts. Methods: A national survey was conducted electronically. A questionnaire was distributed via training program directors and social media to general surgeons across the country, to assess their views on primary anastomosis in perforated diverticulitis. Results: Of the 90 responses to the survey, 72.2% said they would only consider an anastomosis in purulent peritonitis, 18.9% in both faecal and purulent and 8.9% would never consider it. There was a significant difference in choice of operation depending on patient and operative risk factors but no difference between grades of training or subspeciality. Conclusion: The survey showed that high-risk patients are more likely to have an open Hartmann's procedure irrelevant of the grade or subspeciality of the surgeon. The choice of operation in the lower risk patients was varied. Highlights: Primary anastomosis mostly considered in purulent peritonitis from diverticulitis. Operation choice dependent mostly on patient risk factors, some on operative factors. No difference in operation choice depending on grade or subspeciality of training. Malnourishment is the top deterrent for primary anastomosis or Hartmann's reversal.